Cangfudaotan decoction inhibits mitochondria-dependent apoptosis of granulosa cells in rats with polycystic ovarian syndrome - Jiang, Xiao-lin; Tai, He; Xiao, Xuan-si; Zhang, Shi-yu; Cui, Shi-chao; Qi, Shu-bo; Hu, Dan-dan; Zhang, Li-na; Kuang, Jin-song; Meng, Xian-sheng; Li, Shun-min (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is a exceeding universal endocrine and metabolic disorder prevalent in reproductive women, and insulin resistance (IR) is an important pathological factor. Cangfudaotan (CFDT) decoction was applicable to the treatment of gynecological endocrine diseases particularly PCOS, but the underlying mechanism is not clear. In study, 40 Sprague-Dawley (SD) rats (female) were randomized to 4 groups, including control group, PCOS group, PCOS+CFDT group, and PCOS+metformin group. Rats in control group were fed with a normal-fat diet and intraperitoneally injected with 0.5% carboxymethyl cellulose (CMC, 1 mL/kg/d) for 21 days and orally administered saline (1 mL/kg/d) for the next 4 weeks. Rats in PCOS group, PCOS+CFDT group, and PCOS+Metformin group were fed with a high-fat diet (HFD) and intraperitoneally injected with letrozole (1.0 mg/kg) for 21 days, during this period, we recorded the body weights, estrous cycles, and rate of pregnancy in all rats. We examined ovarian ultrastructures of all the rats. We detected blood glucose indexes, serum hormone, and inflammatory factors. Then we detected apoptotic condition, mitochondrial function, and observed mitochondria in ovarian granular cells via transmission electron microscope. We also detected gene of ASK1/JNK pathway in mRNA and protein levels. Those results displayed that CFDT alleviated pathohistological damnification and apoptosis in PCOS rats. In addition, CFDT improved ovarian function, reduced inflammatory response, and inhibited apoptosis of granular cells by improving the mitochondrial function through inhibiting ASK1/JNK pathway. These findings demonstrate that ovary mitochondrial dysfunction appears following PCOS and then induce granular cell apoptosis. CFDT can relieve apoptosis through improving mitochondrial function via inhibiting ASK1/JNK pathway.